Relation Between Corporate Identity And Image: Position Of Attributes And Factors (Theory And Practice) - Žažová, Katarína (Communication Today, 2025)
The study deals with the theme of the relationship of corporate identity and image focusing on the search and analysis of published researches and publications on the topic. The text of study presents processed opinions and practical ﬁndings of domestic and foreign authors. The author characterises corporate identity and image and their mutual relationship. Furthermore, the study describes the characteristics of elements inﬂuencing identity and image of the companies – attributes and factors affecting the image. In the ﬁnal chapter the author states the ﬁndings of predominantly foreign authors who primarily dealt with this topic. The author compares opinions and ﬁndings of other authors and draws her own conclusions. The scientiﬁc methods used while writing the text were analysis, comparison, induction and deduction.